2022
DOI: 10.1021/acs.orglett.2c00182
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Benzannulations of 1-(Indol-2-yl)but-3-yn-1-ols: Easy Access to Functionalized Carbazoles

Abstract: An atom-economical direct synthesis of carbazoles having aryl and aryl ketone groups has been achieved through Pd(II)catalyzed cascade reactions between 1-(indol-2-yl)but-3-yn-1-ols and aldehydes. The reaction proceeds through alkyne−carbonyl metathesis, an uncommon pathway using palladium catalysts, and constitutes a fast intermolecular assembly through four carbon−carbon bond formations in one pot. Absence of the aldehyde substrate resulted in the formation of C4-aryl-substituted carbazoles. The reaction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Subsequent deprotonation at the indole ring followed by reprotonation of the hydroxyl group followed by dehydration and protonolysis leads to the formation of carbazole 71 and the catalyst is regenerated as mentioned in the Schemes 48 and 49 . 132 …”
Section: Lewis Acid Catalysed Synthesis Of Polyfunctional Groups Subs...mentioning
confidence: 99%
“…Subsequent deprotonation at the indole ring followed by reprotonation of the hydroxyl group followed by dehydration and protonolysis leads to the formation of carbazole 71 and the catalyst is regenerated as mentioned in the Schemes 48 and 49 . 132 …”
Section: Lewis Acid Catalysed Synthesis Of Polyfunctional Groups Subs...mentioning
confidence: 99%
“…12 Owing to this importance, a number of strategies for the functionalization of carbazoles and indolines have been developed based on C–H activation protocols. 13 These methods include the transition metal-catalyzed C–H functionalization of carbazoles at the C-1 position and indolines at the C-7 position bearing directing groups with coupling partners for the introduction of alkyl, 14 alkenyl, 15 alkynyl, 16 aryl, 17 acyl, 18 alkoxycarbonyl, 19 amino, 20 amide, 21 arylthio, 22 nitro, 23 cyano, 24 and halide 25 groups (Scheme 1A). Additionally, some important studies on C–H functionalization involving maleimides have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Vieregge and co-workers were the first group to report catalytic CAM reactions in 1959, employing BF 3 as reaction promoter . From developments in the field in the past few decades, it has been established that the CAM reaction can be promoted through either the activation of the carbonyl moiety, which can be achieved by oxophilic Lewis acid (such as FeCl 3 , GaCl 3 , SbF 5 and triflate salts of Zn, Yb, In, and Sc) or Brønsted acid (pTSA, TfOH, TFA, and HBF 4 ) catalysis, or the activation of the alkyne moiety by employing π-electrophilic Lewis acid (such as AgSbF 6 , , AuCl 3 , or Pd-complexes) catalysis. , However, many of these reactions required harsh conditions or used high loadings of transition metal catalysts. Several catalytic systems are applicable to only one type of either intermolecular or intramolecular CAM reactions.…”
mentioning
confidence: 99%